The Association of Glycated Hemoglobin and Lipid Profile with Peripheral Artery Disease in Metabolic Syndrome Patients from Northwestern Algeria - Imane Bouragba; Mustapha Diaf; Sarra Souiah; Asmaa Melih; Attouya Mellali (مجلة بغداد للعلوم)
Glycated hemoglobin (HbA1c) was incorporated as an indicator of dysglycemia, as opposed to fasting glycaemia, for the purpose of classifying patients based on their vascular incidents. This choice was made due to HbA1c's robust correlation with vascular factors like pulse wave velocity, intima media thickness, and the albumin/creatinine ratio (ACR). However, the relationship between HbA1c and lipid profile in developing artery disease remain uncertain. We set out to investigate the association of HbA1c and lipid profile with peripheral artery diseases (PAD) in patients with metabolic syndrome (MetS) in north-western Algeria. Our cross sectional study was carried out during six months. The BMI was calculated as weight(kg)/height2(m2). Ankle-brachial index (ABI)<0.9 and angiography was used to diagnosed PAD and MetS was defined according NCEP-ATPIII criteria. Statistical test, involving correlations and linear regression, were employed to establish the link between HbA1c, fasting glycemia, lipid profile, and the occurrence of PAD in individuals with MetS. In a sample of 300 MetS patients, 53% were male. Positive associations were observed between HbA1c, fasting blood glucose (FBG) (r=0.753, p<0.001), and triglycerides (TG) (r=0.288, p<0.001), with a negative correlation seen with high-density lipoprotein (HDL) (r= -0.356, p<0.001). HbA1c exhibited no significant correlation with total cholesterol (TC) and low-density lipoprotein (LDL). Lipid ratios (LDL/HDL, TC/HDL, TG/HDL) were positively linked to HbA1c (r=0.232, r=0.332 and r=0.43, respectively). Linear regression affirmed these findings. HbA1c displayed positive ties with FBG and TG, while negatively correlated with HDL, showing independence from LDL and TC. Notably, all three lipid ratios showed significant associations with HbA1c